2013
DOI: 10.1603/en13074
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fluctuating Temperatures During Development on Fitness-Related Traits ofScatophaga stercoraria(Diptera: Scathophagidae)

Abstract: Development of ectotherms is highly temperature dependent. Studies using variable thermal environments can improve ecological relevance of data because organisms naturally face day-to-day stochastic temperature fluctuations as well as seasonal changes in the amplitude of such daily fluctuations. The objective of this study was to investigate if, and to what extent, the use of constant temperatures is justified in studies of the model species, yellow dung fly, Scatophaga stercoraria (L.). We examined the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 64 publications
0
33
1
Order By: Relevance
“…These delays are likely a consequence of direct cold or heat injuries and of the costs of subsequent physiological and biochemical repair (23,43). By contrast, FTs that remain within the permissive thermal range can result in diverse responses, including accelerated development (2,13,44,65,66), slower development (25,42,66), or no change in developmental rate (65). One explanation of this variation in responses is that the effect of FTs on the development may depend on the thermal mean that is used and its proximity to developmental thresholds (65).…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These delays are likely a consequence of direct cold or heat injuries and of the costs of subsequent physiological and biochemical repair (23,43). By contrast, FTs that remain within the permissive thermal range can result in diverse responses, including accelerated development (2,13,44,65,66), slower development (25,42,66), or no change in developmental rate (65). One explanation of this variation in responses is that the effect of FTs on the development may depend on the thermal mean that is used and its proximity to developmental thresholds (65).…”
Section: Developmentmentioning
confidence: 99%
“…Accelerated development appears to be the norm if the lower temperature of the FT is not injurious, but falls below a species' thermal threshold for development (93). Finally, the effect of FTs on development time also depends on the 9 amplitude of the variation (14,42,46,66), likely because of Jensen's inequality. For example,…”
Section: Developmentmentioning
confidence: 99%
“…Indeed, Kjærsgaard et al . () advocate the use of more relevant fluctuating temperatures in experimental studies of the ecological impact of climate change.…”
Section: Physiology Individual Performance and Fitnessmentioning
confidence: 99%
“…Likewise, Kjærsgaard et al . () reported that increased temperature variability decreased the individual performance of yellow dung flies Scatophaga stercoraria . Furthermore, some studies have shown that moderate amounts of environmental variability do not necessarily have detrimental effects on performance, compared to greater levels of variability (Pétavy et al, ; Folguera et al, ).…”
Section: Physiology Individual Performance and Fitnessmentioning
confidence: 99%
“…However, thermoperiods can have profound effects on the development time of insects in comparison to constant temperatures (reviewed in Colinet et al, 2015), with an accelerating effect of fluctuating thermal regimes in many cases (Beck, 1983;Ratte, 1984;Fischer et al, 2011;Ragland & Kingsolver, 2008;Kingsolver et al, 2009;Radmacher & Strohm, 2011;Bahar et al, 2012;Kjaersgaard et al, 2013). In our study, we used a thermal fluctuation around a mean temperature of 20 °C, which is much colder than the optimal temperature for this species (around 13 25 °C) (Fleury et al, 2009;Moiroux et al, 2012), and thus is situated in the convex part of its performance curve.…”
Section: Development Timementioning
confidence: 99%